PERANCANGAN VISUAL BRANDING KOTA PADANGSIDIMPUAN - ANNISA FAUZIAH, Drs. Syafwandi, M.Sn., Dini Faisal, S.Ds., M.Ds (DEKAVE : Jurnal Desain Komunikasi Visual, 2015)
Padangsidimpuan is a town in the province of North Sumatra that geographically surrounded by South Tapanuli. Padangsidimpuan as a city which uphold the cultural values is less well known of Indonesian society because the lack of city promotion by the government. Therefore, the authors was designing the visual branding that summarized in the manual book and than become a guideline for the government to apply to the various media.The design of the visual branding logo is taken from the form of fruits and leaves are typical of the city of Padangsidimpuan. Then use motifs that have been adapted to the character Padangsidimpuan City. As well as the use of the concept and philosophy of culture, color and script entirely serve as the idea of designing a logo that also have headline and tagline Salumpat Saindege who also became the motto of the City Padangsidimpuan.The main design is the logo, tagline and icons. The main media used in the design of visual branding Padangsidimpuan City is manual book. Then the supporting media them wallpaper Padangsidimpuan City buses, totebag, mugs, calendars, T-shirts, flag chain, posters, stickers, key chains, and umbrella.Key Words : Visual Branding, Padangsidimpuan, Media